Utilización de polvo secante poultry liptosa nido en la cama de pollos broilers a escala comercial - Peralta Celi, Zachary Cristopher (2014)
One of the reasons for this research was to learn more about the reality of poultry farming in our country, specifically in our province in terms of economic and health . This research was made El Cantón Balsas de la provincia de El Oro, in the poultry farm AVICOMZA company in February of 2013. I worked with a total of 21992 birds, divided into 3 lots. The first batch with 8552 birds, the second batch with 8500 birds and bird’s third batch 4940, in all the batches were working with a population density of 8.5 birds per m2. The research work consisted in using drying power (POULTRY LIPTOSA NIDO) in the amount of 150, 175 and 200 g /m2, respectively, in order to reduce ammonium levels in the environment by improving environmental conditions, and evaluate economic and sanitary between 3 lots, the cost-benefit ratio. Achieving determine, noting all the above, were obtained the lot 1 gender.